A Rare and Unexpected Reason for Unilateral Epistaxis: Nasal Septal Schwannoma - Alper Yenigun; Yasin Kulaksiz; Tugce Esen Kiran; Erol Senturk; Fadlullah Aksoy; Orhan Ozturan (Case Reports in Otolaryngology)
Nasal septal schwannoma is a rare tumor. It causes complaints such as nasal congestion, nosebleeds, and headaches. There are many diseases such as nasal polyps, antrochoanal polyp, chronic rhinosinusitis, concha bullosa, inverted papilloma, and retention cyst with schwannoma diagnosis. The diagnosis is made histopathologically, and the treatment is surgery. In this case report, we presented a male patient with septal schwannoma who had nasal obstruction for a year and reviewed the last 20 years of literature on nasal schwannoma.